English Clickbait Language Features Which Attract Thai Tertiary EFL Learners - Srimanoi, Wipatsaya; Boonmoh, Atipat (rEFLections, 2025)
This study explored how likely its Thai participants were to choose to read an article with a clickbait headline, together with how the reasons given for choosing clickbait headlines correspond to the linguistic features found in the headlines. News headlines were presented to 18 participants to rate which news headline they would choose. Then, the rationales behind the selection were elicited using an interview. The results revealed that the majority of the participants preferred non-clickbait headlines because they consider the relevancy of the headlines to themselves as the major factor, followed by the linguistic features of the headline, which marked education as not relevant to choosing to read a news headline. Among the headlines selected, numbers and unanswered questions play a vital role in influencing people to choose non-academic headlines. Numbers make the headline easier to follow and look reliable, while unanswered questions prompt the reader to discover the truth. All in all, clickbait is not as ‘clickbaity’ when personal relevance and preference affect headline selection. Here, personal relevance includes background, interest, and age, whereas personal preference includes entertaining content, use of neutral words, non-question type headlines, and use of formal words used.